Dynamic efficiency and economic complexity. (28th February 2022) - Moreno‐Casas, Vicente; Bagus, Philipp
Abstract: This article deals with the link between complexity economics and the Austrian concept of dynamic efficiency. The conventional notion of efficiency used in economic science, regarded as static in this article, is rejected for being incompatible with complexity economics in epistemic terms. The concept of dynamic efficiency is thus presented as an alternative definition of efficiency, given its epistemic and theoretical similarities with complexity economics; more concretely, with Santa Fe complexity. Consequently, a direct, causal relationship between economic complexity and dynamic efficiency is highlighted. This relationship is confirmed in light of recent applications of both dynamic efficiency theory and complexity economics to the study of economic development. Finally, it is pointed out that economic complexity and dynamic efficiency can be combined to improve our understanding of the development process.